Influence of Heat and Mass Transfer on Free Convection of Micropolar Fluid between Vertical Concentric Cylinders - A. K. Singh; A. K. Singh (Journal of Applied Fluid Mechanics, 2019)
Natural convective flow of a micropolar ﬂuid is examined analytically in order to see the effect of heat and mass transfer between two concentric vertical cylinders of infinite length. The governing equations of model in non-dimensional form corresponding to the temperature, velocity and microrotational velocity, using the Boussinesq approximation and Eringen equation with suitable boundary conditions are expressed in terms of cylindrical coordinate system and then their exact solutions are obtained. The influence of the non-dimensional physical parameters such as the material and vortex viscosity parameters on the velocity, microrotational velocity is evaluated by showing on the graphs while the values of skin friction in non-dimensional form at the outer and inner surfaces of inner and outer cylinders have been presented in the tabular form.